2011
DOI: 10.1007/s00134-011-2300-7
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations on basic requirements for intensive care units: structural and organizational aspects

Abstract: Objective: To provide guidance and recommendations for the planning or renovation of intensive care units (ICUs) with respect to the specific characteristics relevant to organizational and structural aspects of intensive care medicine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
170
0
27

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 290 publications
(223 citation statements)
references
References 60 publications
4
170
0
27
Order By: Relevance
“…We point out here that, as reported in [41], an ICU should accommodate between 8 and 12 beds. From [11, Table 2], where authors apply structured and standard hidden Markov models for estimating the transmission rate of MRSA among patients within a hospital, we consider a general transmission rate for a well-mixed population of patients equal toβ = 0.329 days −1 .…”
Section: Numerical Resultsmentioning
confidence: 50%
See 1 more Smart Citation
“…We point out here that, as reported in [41], an ICU should accommodate between 8 and 12 beds. From [11, Table 2], where authors apply structured and standard hidden Markov models for estimating the transmission rate of MRSA among patients within a hospital, we consider a general transmission rate for a well-mixed population of patients equal toβ = 0.329 days −1 .…”
Section: Numerical Resultsmentioning
confidence: 50%
“…(1), β =β/9 represents in our model the rate at which each susceptible patient is infected by each infected patient under homogeneous mixing assumptions. We introduce heterogeneity in our model in order to analyse two different control strategies commonly implemented to avoid outbreaks of MRSA: (i) a proper organisation of rooms, trying to configure the ICU in an uncrowded fashion when possible [41], and (ii) the isolation of the individual which is found to start an outbreak within the ICU [14]. Thus, when patient 1 initiates the outbreak (initial state x = (I, S, .…”
Section: Numerical Resultsmentioning
confidence: 99%
“…There is no substitute for an adequate number of critical care beds to which appropriate surgical patients can be admitted. 17,18,25 In our busy public sector hospitals with financial and organizational constraints, we suggest allocation of a dedicated isolated space in the vicinity of wards in the form 4-6 bedded High Dependency Unit can cover all essential aspect of management of critical surgical patients.…”
Section: Discussionmentioning
confidence: 99%
“…21 A survey 17 of intensivists on patient to intensivist ratios indicated that the mean ratio of patient to attending physician was 13 to 1, with an upper limit of 24 to 1 at night. In that study, 17 factors that affected physician to patient ratios included number of ICU beds, mean daily census, and maximum service size (number of physicians).…”
Section: Discussionmentioning
confidence: 99%